Dynamic Interleukin-1 Receptor Type 1 Signaling Mediates Microglia-Vasculature Interactions Following Repeated Systemic LPS - Nemeth DP; Liu X; McKim DB; DiSabato DJ; Oliver B; Herd A; Katta A; Negray CE; Floyd J; McGovern S; Pruden PS; Zhutang F; et al. (Dove Medical Press, 2022)
Daniel P Nemeth,1- 3 Xiaoyu Liu,3 Daniel B McKim,4 Damon J DiSabato,2,5 Braedan Oliver,2 Anu Herd,3 Asish Katta,1 Christina E Negray,1,2 James Floyd,3 Samantha McGovern,3 Paige S Pruden,2 Feiyang Zhutang,2 Maria Smirnova,3 Jonathan P Godbout,2,5 John Sheridan,1,2 Ning Quan3 1College of Dentistry, The Ohio State University, Columbus, OH, USA; 2Institute for Behavioral Medicine Research, The Ohio State University, Columbus, OH, USA; 3Stiles-Nicholson Brain Institute, Florida Atlantic University, Jupiter, FL, USA; 4Department of Animal Sciences, University of Illinois Urbana-Champaign, Champaign, IL, USA; 5Department of Neuroscience, The Ohio State University, Columbus, OH, USACorrespondence: Daniel P Nemeth; Ning Quan, 5353 Parkside Drive, Jupiter, FL, 33458, USA, Email nemethd@fau.edu; nquan@health.fau.eduIntroduction: Lipopolysaccharide (LPS) preconditioning involves repeated, systemic, and sub-threshold doses of LPS, which induces a neuroprotective state within the CNS, thus preventing neuronal death and functional losses. Recently, proinflammatory cytokine, Interleukin-1 (IL-1), and its primary signaling partner, interleukin-1 receptor type 1 (IL-1R1), have been associated with neuroprotection in the CNS. However, it is still unknown how IL-1/IL-1R1 signaling impacts the processes associated with neuroprotection.Methods: Using our IL-1R1 restore genetic mouse model, mouse lines were generated to restrict IL-1R1 expression either to endothelia (Tie2-Cre-Il1r1r/r) or microglia (Cx3Cr1-Cre-Il1r1r/r), in addition to either global ablation (Il1r1r/r) or global restoration of IL-1R1 (Il1r1GR/GR). The LPS preconditioning paradigm consisted of four daily i.p. injections of LPS at 1 mg/kg (4d LPS). 24 hrs following the final i.p. LPS injection, tissue was collected for qPCR analysis, immunohistochemistry, or FAC sorting.Results: Following 4d LPS, we found multiple phenotypes that are dependent on IL-1R1 signaling such as microglia morphology alterations, increased microglial M2-like gene expression, and clustering of microglia onto the brain vasculature. We determined that 4d LPS induces microglial morphological changes, clustering at the vasculature, and gene expression changes are dependent on endothelial IL-1R1, but not microglial IL-1R1. A novel observation was the induction of microglial IL-1R1 (mIL-1R1) following 4d LPS. The induced mIL-1R1 permits a unique response to central IL-1β: the mIL-1R1 dependent induction of IL-1R1 antagonist (IL-1RA) and IL-1β gene expression. Analysis of RNA sequencing datasets revealed that mIL-1R1 is also induced in neurodegenerative diseases.Discussion: Here, we have identified cell type-specific IL-1R1 mediated mechanisms, which may contribute to the neuroprotection observed in LPS preconditioning. These findings identify key cellular and molecular contributors in LPS-induced neuroprotection.Graphical Abstract: Keywords: BBB, neuroinflammation, perivascular microglia